Rapid Antibacterial Activity of Cannabichromenic Acid against Methicillin-Resistant Staphylococcus aureus - Maria Galletta; Tristan A. Reekie; Gayathri Nagalingam; Amy L. Bottomley; Elizabeth J. Harry; Michael Kassiou; James A. Triccas (MDPI AG, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) has proven to be an imminent threat to public health, intensifying the need for novel therapeutics. Previous evidence suggests that cannabinoids harbour potent antibacterial activity. In this study, a group of previously inaccessible phytocannabinoids and synthetic analogues were examined for potential antibacterial activity. The minimum inhibitory concentrations and dynamics of bacterial inhibition, determined through resazurin reduction and time-kill assays, revealed the potent antibacterial activity of the phytocannabinoids against gram-positive antibiotic-resistant bacterial species, including MRSA. One phytocannabinoid, cannabichromenic acid (CBCA), demonstrated faster and more potent bactericidal activity than vancomycin, the currently recommended antibiotic for the treatment of MRSA infections. Such bactericidal activity was sustained against low-and high-dose inoculums as well as exponential- and stationary-phase MRSA cells. Further, mammalian cell viability was maintained in the presence of CBCA. Finally, microscopic evaluation suggests that CBCA may function through the degradation of the bacterial lipid membrane and alteration of the bacterial nucleoid. The results of the current study provide encouraging evidence that cannabinoids may serve as a previously unrecognised resource for the generation of novel antibiotics active against MRSA.